Caecal duplication cyst: rare case report with review of literature - J., Muthukumaran; V., Udhayasankar (International Surgery Journal, 2019)
Duplication cysts of the alimentary tract are very rare congenital anomaly. Out of all these cases, two-thirds of them manifest before the age of 2 years. They are common in ileum, but very rare in cecum. We hereby report a case of 6 years female child presented in paediatric surgery department with abdominal pain, diagnosed as duplication cyst with intussusceptions.